ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Fuadiantoni, Rahmad; ., Suratna; Mulyanto, Indro Herry (Jurnal Ilmu Administrasi dan Bisnis, 2018)
This study aims to determine the factors that affect the capital structure of coal companies listed on the Indonesia Stock Exchange either partially or simultaneously. This type of research is explanatory research. The sampling technique used is purposive sampling with amount of sample 19 coal companies listed on the Indonesia Stock Exchange. The analysis technique used multiple linear and hypothesis testing using partial t-test with a level of significance of 5%. The result of this research, asset structure has significant effect to capitalstructure, operating leverage has a significant effect on capital structure, the level of sales growth has a significant effect on capital structure, profitability has a significant effect on capital structure, and liquidity significantly affects the capital structure. Asset structure, operating leverage, sales growth rate, profitability, and liquidity simultaneously have a significant effect on the capital structure. Based on research finding, companies should have plans and strategies in financial management to establish an optimal capital structurein order to maximize company profits and value. By considering these factors it is expected that the management will be easier in determining the optimal capital structure.Keywords: capital structure (DER), asset structure, operating leverage (DOL), sales growth rate, profitability (ROA), liquidity (CR).